Adsorption and Desorption Properties of Coalbed Methane on SBA-15 - Zheng, Wenxiang; Liu, Zhenghe; Yang, Lusheng (Asian Journal of Chemistry, 2014)
The adsorption and desorption properties of coalbed methane on SBA-15 and activated carbon (AC) with the same process were investigated. For the three adsorbents, the adsorption capacity to coalbed methane is the following sequence, activated carbon > SBA-15. The results showed that coalbed methane desorbed from the surface of SBA-15 is easily compared with the other materials. However activated carbon is easier than both of them. Both of adsorption capacity and adsorption strength of SBA-15 sample to coalbed methane are lower than the other two adsorbents, most likely due to the pore diameter of the SBA-15 sample is larger to the molecular diameter of methane. However SBA-15 sample has a larger pore size and specific surface area relative to conventional materials sample, which result in a large value of adsorption capacity of modified SBA-15 sample to coalbed methane. In addition, although the adsorption capacity of SBA-15 sample to coalbed methane is lower in contrast to activated carbon, modified SBA-15 sample is easy to regenerate and has a short time of desorption. Hence, SBA-15 sample, as an adsorbent, is a good choice for the condition of low concentration of coalbed methane.